"Una opción sutil de protestar:" Literary Magazines, Subterranean Resistance, and Life Politics in Putumayo, Colombia. Issue 3 (13th January 2022) - Shepard, Mathilda
Abstract : This article examines the poetics of resistance in Katharsis: la revista literaria del Putumayo . Established during the occupation of southwestern Colombia by right-wing paramilitary forces (1997–2006), Katharsis describes itself as both the "literary door to Putumayo" and a "strategy of resisting war." While cultural studies have offered valuable insights into the acts of witnessing, mediating, and critiquing violence in Colombia, the question of resistance – a concept situated between thought and action, representation and concrete practice – remains understudied. I propose that Katharsis engages in "subterranean resistance", or a strategy of working beneath the surface of what is visibly political to promote other ways of thinking, feeling, and living in militarised spaces. By critically engaging the relational space of territory, Katharsis constructs modes of representing and inhabiting Putumayo that diverge from the territoriality of paramilitarism. The magazine anchors subterranean resistance in a "life politics" (Lyons 2016 ) that situates human life within the more-than-human ecologies of the selva. In doing so, it links Putumayo to other geographies negatively impacted by extractivism, chemical warfare, and parastate violence across the Global South.